2017
DOI: 10.1210/en.2017-00686
|View full text |Cite
|
Sign up to set email alerts
|

GADD45a Promotes Active DNA Demethylation of the MMP-9 Promoter via Base Excision Repair Pathway in AGEs-Treated Keratinocytes and in Diabetic Male Rat Skin

Abstract: Diabetes elevates matrix metalloproteinase (MMP)-9 levels in the skin and its keratinocytes, and activated MMP-9 impairs skin wound healing. Epigenetic regulation of the DNA methylation status within the MMP-9 promoter plays an important role in the alteration of MMP-9 expression. Our aim was to investigate the role and mechanism of growth arrest and DNA damage-inducible 45a (GADD45a), a well-known DNA demethylation regulatory protein that mediates DNA methylation, in the regulation of MMP-9 expression. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…DNMT1, which was DE at an advanced stage in MAP-infected JD(-) macrophages, is necessary to establish and maintain DNA methylation patterns (132). GADD45A was strongly downregulated and therefore probably does not favor active DNA demethylation (57). Together, these results suggest the preservation of DNA methylation patterns at the sequence level.…”
Section: Immune Tolerance In Perspective To Explain Refractory State mentioning
confidence: 75%
See 1 more Smart Citation
“…DNMT1, which was DE at an advanced stage in MAP-infected JD(-) macrophages, is necessary to establish and maintain DNA methylation patterns (132). GADD45A was strongly downregulated and therefore probably does not favor active DNA demethylation (57). Together, these results suggest the preservation of DNA methylation patterns at the sequence level.…”
Section: Immune Tolerance In Perspective To Explain Refractory State mentioning
confidence: 75%
“…During the initial "cytokine storm" (section inflammatory processes), the gene expression of DNA methyltransferase 1 (DNMT1), responsible for gene hypermethylation, increased ∼2-fold at 24 hpi (Supplementary Table 4). The growth arrest and DNA-damage-inducible protein 45 alpha (GADD45A) and gamma (GADD45G) genes are members of a small family of stress-response genes and serve as a nexus between DNA repair and epigenetics (57). The GADD45A and GADD45G genes were downregulated from 4 hpi until 24 hpi in MAP-infected JD(-) macrophages ( Supplementary Table 4).…”
Section: Putative Epigenetic Modifiers In the Second Wave Of Gene Expmentioning
confidence: 99%
“…Diverse studies have shown that AGEs are involved in various tissue pathologies arising from diabetic complications, including vessels, skin, bone, kidney and periodontal tissues . Kume et al reported that fat, cartilage and bone differentiation from MSCs were reduced following artificially supplemented AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the role played by epigenetic mechanisms in the well-studied phenomenon of metabolic memory of diabetes [149]. The pathological effects of hyperglycemia are due to four basic mechanisms: PKC activation, enhanced production of AGEs, enhanced glucose flux due to polyol pathway, and upregulation of hexosamine 11 Oxidative Medicine and Cellular Longevity pathway activity [150,151]. Hyperglycemic status has been associated with the activation of histone modifications that provoke the enhanced expression of inflammatory genes [152].…”
Section: Epigenetic Effects Of Agesmentioning
confidence: 99%